Clinical Benefits of the Immediate Implant Socket Shield Technique. Issue 2 (12th February 2017) - Saeidi Pour, Reza; Zuhr, Otto; Hürzeler, Markus; Prandtner, Otto; Rafael, Caroline Freitas; Edelhoff, Daniel; Liebermann, Anja
ABSTRACT: Objective: Extraction‐socket resorption is considered a major problem that can limit implantological rehabilitation options and compromise the esthetic outcome. Surgical techniques to reduce remodeling are of restricted predictability and commonly require several surgical interventions and grafting. This increases the treatment cost and places a physical and psychological strain on the patient. This clinical case report presents a replacement of an upper canine using the socket‐shield technique (SST) with a CAD/CAM surgical guide, resulting in a predictable, high esthetic, and functional result. Clinical considerations: The SST is an alternative approach to curbing remodeling and resorption by retaining the facial part of the root during tooth extraction. An immediately placed implant supports the facial root fragment, preventing the collapse of the buccal wall. The SST with digital precision planning in combination with a CAD/CAM surgical guide benefits patients by preserving their tissue architecture and causing only insignificant trauma. Furthermore, the SST reduces the number of surgical and prosthetic interventions required to one each for pre‐operative planning, surgical procedures, and prosthetic rehabilitation. Conclusions: The socket shield technique is a minimally invasive implantological approach offers patients and clinicians multiple benefits. Clinical Significance: The socket‐shield technique (SST) represents an alternative approach to intervene remodeling and resorption processes by the maintenance of the facial part of the root during tooth extraction. The immediate placement of an implant supports the facial root fragment and thereby prevents a collapse of the buccal wall. The SST associated with a CAD/CAM fabricated surgical guide, can reduce the amount of appointments, due to the immediate fabrication of the definitive restoration with the existing model. Therefore, no further necessary appointments are required apart from first pre‐operative planning, second for surgical treatment, and third for prosthetic rehabilitation. (J Esthet Restor Dent 29:93–101, 2017)